Beginning responsive web design with HTML5 and CSS3 - Fielding, Jonathan (Expert's voice in Web development., 2014)
Beginning Responsive Web Design with HTML5 and CSS3 is your step-by-step guide to learning how to embrace responsive design for all devices. You will learn how to develop your existing HTML, CSS, and JavaScript skills to make your sites work for the modern world. Web sites and apps are now accessed on a wide range of devices with varied sizes and dimensions, so ensuring your users have the best experience now means thinking responsive. In Beginning Responsive Web Design with HTML5 and CSS3 you will learn about all aspects of responsive development. You'll start with media queries, and fluid CSS3 layouts. You'll see how to use responsive frameworks such as Twitter Bootstrap, and how to use tools such as Grunt, Bower, Sass, and LESS to help save you time. You'll also learn how to use JavaScript to manage responsive states, manage your user's journey across screen sizes, and optimize your responsive site. By the end of the book you will be able to build new sites responsively, and update existing sites to be responsive. Every aspect of a responsive build will be covered. This book is perfect for developers who are looking to move into the future of responsive sites. Whether you have already dipped your toes into responsive development or are just getting started, Beginning Responsive Web Design with HTML5 and CSS3 will teach you the very best techniques to optimize your site and your user's experience.- Resumé vydavatel